A Comprehensive Systematic Review of The Association between Low-Carbohydrate Diet and Weight Loss in Morbidly Obese Patients - Mohamad Fadli; Hendandy Driya Pamungkas (International Medical Journal Corp. Ltd, 2026)
Introduction: Morbid obesity (BMI ≥40 kg/m² or ≥35 kg/m² with comorbidities) presents a significant global health challenge with limited effective non-surgical interventions. Low-carbohydrate diets (LCD) have emerged as potential therapeutic approaches, but their efficacy and safety in morbidly obese populations remain incompletely characterized. This systematic review synthesizes evidence from randomized controlled trials and cohort studies examining LCD effects on weight loss and metabolic outcomes in morbidly obese patients. Methods: We systematically screened studies based on predefined criteria: morbidly obese participants (BMI ≥40 kg/m² or ≥35 kg/m² with comorbidities), LCD intervention (≤130g carbohydrates daily or ≤26% total energy), reported weight loss outcomes, study duration ≥4 weeks, and non-surgical dietary focus. Data extraction encompassed study characteristics, intervention details, comparator groups, weight loss outcomes, metabolic parameters, effectiveness moderators, and safety parameters. Results: Eighty studies comprising diverse populations (mean BMI 27-43 kg/m²) were included. LCD demonstrated superior short-term weight loss at 3-6 months compared to control diets, with mean differences ranging from -2.0 kg (95% CI: -3.1 to -0.9) in meta-analyses to -5.8 kg versus -1.9 kg (p=0.002) in individual trials. Very low-carbohydrate ketogenic diets (VLCKD) achieved the most dramatic initial results (13.6±3.9 kg loss at 2 months). At 12 months, advantages diminished but remained detectable (mean difference -0.93 kg; 95% CI: -1.81 to -0.04). Long-term follow-up (≥18 months) revealed weight regain patterns with convergence between dietary approaches. In diabetic populations, LCD produced superior glycemic control (HbA1c reductions of -0.61% to -1.5%) and medication reduction (95.2% of participants reduced/eliminated diabetes medications). Metabolic improvements included triglyceride reductions (-29.71 mg/dL; 95% CI: -31.99 to -27.44), HDL increases (+1.73 mg/dL; 95% CI: 1.44 to 2.01), and blood pressure reductions, though LDL responses were variable with increases observed in some studies. Safety profiles were generally favorable with transient adverse effects (constipation, fatigue, headaches) and no serious adverse events requiring medical attention. Discussion: LCD effectiveness is mediated through multiple mechanisms including glycogen depletion, ketosis-induced appetite suppression, spontaneous caloric reduction, and improved insulin dynamics. Effectiveness moderators include baseline characteristics (diabetes status, sex, central obesity), carbohydrate restriction intensity, adherence levels, and support intensity. Long-term convergence reflects decreasing adherence, metabolic adaptation, and similar energy intake between groups. Population-specific advantages favor LCD in type 2 diabetes and metabolic syndrome. Conclusion: Low-carbohydrate diets represent effective short-to-intermediate term interventions for weight loss in morbidly obese patients, with particularly robust benefits in diabetic populations. Optimal implementation requires intensive behavioral support, appropriate patient selection, regular monitoring of metabolic parameters (especially LDL cholesterol), and realistic expectations regarding long-term weight maintenance challenges. Future research should focus on strategies to enhance long-term adherence and identify genetic/biological predictors of differential response.